Acute Myocardial Infarction due to Coronary Artery Embolism in a Patient with Mechanical Aortic Valve Prosthesis - Marcelo A. Nakazone; Bruno G. Tavares; Maurício N. Machado; Lilia N. Maia (Case Reports in Medicine)
Previous cases of coronary embolism as a cause of myocardial infarction (MI) in association with prosthetic mechanical valves have been reported, but the fact that the patient was not aware of the importance of maintaining anticoagulation therapy is relevant in this case. A 16-year-old female was referred for primary coronary intervention due to subacute anterolateral ST elevation MI, after she decided to discontinue warfarin therapy three weeks before. Coronary angiography showed distal occlusion of the left anterior descending coronary artery with an image suggesting embolic material. Conventional echocardiography demonstrated akinesia of anteroseptal, inferior, and posterior segments of the left ventricle, with severe systolic dysfunction, beyond the intraventricular thrombus. The presence of mechanic aortic prosthesis and no anticoagulation therapy are highly suggestive of coronary embolism as the cause of MI. This case report confirms that patient education is vital in our struggle to prevent this complication in high-risk patients.